Social media at workplace: A case study of employees' productivity at Terengganu Foundation, Terengganu / Syahirah Hadirah Hashim - Hashim, Syahirah Hadirah (Faculty of Business Management, 2018)
The purpose of this paper is to investigate the relationship between the factors of social media towards employees' productivity in Terengganu Foundation, Kuala Terengganu. A total of 108 sets of questionnaires were distributed to the employees at Terengganu Foundation by using systematic sampling. The response rate in this study was 91.6 percent. Researcher discovered that the factors of social media positively give impact to employee's productivity. It also found that the factors of social media have a positive relationship with employee's productivity. Researcher suggests management of companies to encourage the usage of social media, create campaign and conduct training program in order to increase the awareness of using social media at the workplace. As a conclusion, this paper has revealed the importance of social media at the workplace would increase employee's productivity.